STRATEGI PSIKOLOGI DAKWAH DALAM MENCEGAH RADIKALISME REMAJA MELALUI INTERNALISASI NILAI-NILAI MODERASI BERAGAMA - Sholeha, Jami'atus; Puspitasari, Ema (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Abstract Radicalism among adolescents is a serious problem that requires a specific approach. This research aims to develop a strategy for preventing radicalism thru the internalization of religious moderation values (Wasathiyyah) using a da'wah psychology approach. The method used is a qualitative literature study with an analysis of various literature related to da'wah psychology, adolescent development, and religious moderation. The research results show the effectiveness of the three-stage value internalization model: (1) value receiving thru the introduction of the principles of al-tawassuth and al-tasamuh using creative media; (2) emotional responding thru group discussions and conflict simulations to instill al-i'tidal and al-tawazun; and (3) identity organizing thru mentoring programs and real-world actions. This strategy successfully addresses three factors that contribute to radicalism in adolescents: identity crisis, the need for group recognition, and cognitive conflict. This research makes a significant contribution to the development of a humanistic and contextual preventive da'wah model, particularly for shaping a moderate and tolerant young generation.